Kajian Perubahan Luas Laguna di Pantai Samas, Kabupaten Bantul dengan Menggunakan Citra Satelit Landsat Multi-temporal - Saputra, Rifky; Subardjo, Petrus; ADS, Agus (977-2407769)
Samas beach lagoon is a unique and rare ecosystem, as well as being an area of tourism. One of the great river that empties into the Laguna Samas carry sediment material which will further lead to changes in the shape of land in the area. One impact of the change in shape in the area is the ever-expanding or narrowing of the land caused by the process of sedimentation. Sedimentation process is rapid and continuous this will damage the ecosystem Laguna Samas. To overcome this need to be monitoring the events that lead to environmental degradation. This activity is necessary to obtain accurate data and information and the actual on coastal and marine issues being faced today. The method used in this research is descriptive method, which is a study to create a picture of the situation or event that researched and studied in a limited time and place, to get an idea of the situation or conditions locally. In addition, this study also uses remote sensing techniques (visual interpretation using screen digitalizing techniques and field surveys). The material used in this study are Landsat images. Within 15 years, Laguna Samas and extensive changes shape significantly. Vast changes that have occurred in the lagoon research in the period between 1994 to 2001 had an area of 45.53 ha of erosion and accretion area of 13.58 ha. Changes vast lagoon in 2001 to 2005 was eroded area of 58.86 ha and 36.39 ha area accretion. And extensive changes in the lagoon in 2005 to 2011 had an area of 28.07 ha of erosion and accretion area of 58.38 ha. So, in 1994 until 2005, it had added vast lagoon waters, and in 2005 to 2011 extensive shrinkage or constriction waters. These results were obtained from the Landsat 5 satellite imagery overlay TM in 1994, Landsat 7 ETM 2001, Landsat 7 ETM 2005 and Landsat 7 ETM in 2011.